Seminar On Entrepreneurial Spirit Of Export Business: (Operational And Financial Aspect) - Karisma Wati; M.Alkadri Perdana (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This seminar is an activity carried out to help students and the community in increasing the entrepreneurial spirit of export business. The seminar method was chosen because it is more effective in delivering and receive materials. The main objectives of the project to be achieved in this final project is to create or organize seminars on improving the entrepreneurial spirit of export businesses. Find and determine sponsorship criteria, find speakers who understand about the export business, register participants, know budget planning and realization during operations, know the obstacles that occur, find solutions to these obstacles Meet and evaluate seminar activities through feedback from participants. The project results show that the technical aspects of operational and financial work in the implementation activities are divided into several stages, namely the stage of finding sponsors, determining operational budgets, constraints that occur, solutions to obstacles faced and project evaluation. The research results seminar was held on Tuesday, 07 November 2023 at the Mini Conference Hall GKT 1 Bengkalis State Polytechnic from 13:30-16:10 WIB. The seminar can run smoothly thanks to the teamwork consisting of 14 committee members. In this agenda there was one speaker and 132 participants who attended. The technical aspects of work in the implementation of activities are divided into several stages, namely the project preparation stage, the project implementation stage, project completion and project reporting.